ANALISIS SEKTOR EKONOMI UNGGULAN DAN PERGESERAN STRUKTUR PEREKONOMIAN KOTA BATU TAHUN 2012-2016 - Nadya Bella Silvya; Wahyu Hidayat; Yunan Syaifullah (Jurnal Ilmu Ekonomi JIE, 2019)
Economic development must include economic growth, where economic development greatly encourages economic growth and economic growth facilitates the process of economic development. With this to know the leading economic sectors in the economy in Batu City in 2012-2016. By using analysis tools Merging Static Location Quotient (SLQ) and Dynamic Location Quotient (DLQ), Klassen Typologies and Shift-Share.The research results obtained that in Batu City based on the analysis of the Merger of Static Location Quotient (SLQ) and Dynamic Location Quotient (DLQ) belonging to the superior economic sector is the economic sector of Construction. The Klassen Typology analysis, which is classified as a fast-developing and fast-growing sector, is the Construction, Large and Retail Trade sector; Reparas for Cars and Motorbikes, Provision of Accommodation and Food Drinking,   Information and Communication, and Other Services. While, the Shift-Share analysis which is classified as capable of competing or competitive is the sector of Large Trade and Retail; Repair of Cars and Motorbikes, Provision of Accommodation and Food Drinking, and Construction.